1999
DOI: 10.1097/00007632-199909150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Radiofrequency Lumbar Facet Denervation for Chronic Low Back Pain

Abstract: Radiofrequency lumbar zygapophysial joint denervation results in a significant alleviation of pain and functional disability in a select group of patients with chronic low back pain, both on a short-term and a long-term basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
396
3
10

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(413 citation statements)
references
References 38 publications
4
396
3
10
Order By: Relevance
“…According to results of several clinical trials, RF denervation of lumbar facet joints seems to be a very effective therapy with a success rate of 43-87% after 1 year [7,12,13]. Compared to those trials, 22% success rate of our study in 1 year after therapy is disappointing.…”
Section: Discussioncontrasting
confidence: 62%
“…According to results of several clinical trials, RF denervation of lumbar facet joints seems to be a very effective therapy with a success rate of 43-87% after 1 year [7,12,13]. Compared to those trials, 22% success rate of our study in 1 year after therapy is disappointing.…”
Section: Discussioncontrasting
confidence: 62%
“…Radiofrequency denervation vs sham treatment for chronic facet joint pain The Cochrane review included three trials that showed conflicting evidence on the short-term effect of radiofrequency lesioning on pain and disability [34,57,93]. One trial found that radiofrequency denervation statistically significantly reduced pain intensity and improved functioning at 2 month follow-up [93].…”
Section: Effectiveness For Chronic Low Back Painmentioning
confidence: 99%
“…One trial found that radiofrequency denervation statistically significantly reduced pain intensity and improved functioning at 2 month follow-up [93]. Another trial showed greater improvement in RolandMorris score but not in either Oswestry score or pain score at 4 week follow-up [57].…”
Section: Effectiveness For Chronic Low Back Painmentioning
confidence: 99%
“…A 22-gauge needle, 100-mm RF electrode, and active 5-mm tip were used. The cannula tip was placed using the "tunnel vision," per van Kleef et al (15). Once the tip needle was at the target, sensory stimulation was carried out at 50 Hz up to 0.5 V to confirm the proximity to the medial branch.…”
Section: Methodsmentioning
confidence: 99%